(untitled) (International journal of artificial intelligence, 2026)
In the modern digital environment, web applications have become a primary platform for storing, processing, and transmitting sensitive user information, including personal data, authentication credentials, and financial records. As the number of cyber threats and data breaches continues to increase, ensuring the confidentiality, integrity, and availability of user data has become a critical challenge for web developers and organizations. This study focuses on the role of encryption and data protection technologies in enhancing web application security. The paper examines both symmetric and asymmetric cryptographic algorithms, secure communication protocols, hashing mechanisms, and authentication strategies used to protect user information from unauthorized access and malicious attacks. The research analyzes widely adopted encryption standards such as AES, RSA, and ECC, as well as modern transport-layer security protocols including HTTPS and TLS. Additionally, the study explores best practices for secure password storage, data encryption at rest and in transit, and the integration of encryption mechanisms within modern web architectures. Through a systematic methodology, the effectiveness of these technologies is evaluated in terms of security strength, performance impact, and implementation complexity. The findings highlight the importance of adopting a layered security approach and demonstrate that properly implemented encryption technologies significantly reduce the risk of data leakage and cyberattacks. The results of this research provide practical recommendations for developers and organizations aiming to build secure, trustworthy, and resilient web systems.